Correlation between Emotional Intelligence and Workplace Flourishing among Nurses Working in Critical Care Units - Hasnaa S. Abdelkreem; Karima A. Zaid; Ali H. Alhayati; Shaimaa S. Adam (Evidence-Based Nursing Research)
Context: Emotional intelligence is a group of skills not related to mental capabilities and includes social competencies that enhance an individual's flourishing when confronting daily needs and stress. Emotional intelligence is crucial to one's intelligence for many people to achieve ascendency in their lives and professional careers. As human beings, success and, specifically, professional advancement relies upon a person's ability to recognize other personnel's signals and react to them appropriately.